2001
DOI: 10.1002/chin.200136271
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Hetisane‐Type Diterpenoid Alkaloids

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…When the fragmentor voltage increased to 375 V, it produced three minor fragment ions at m/z 312.1974, 294.1865 and 266.1867 by consecutive losses of H 2 O, H 2 O and CO. Compared with the literature reports (Rashkes et al , ; Bessonova and Saidkhodzhaeva, ), it could be tentatively identified as hetisine. Compound 14 ( m/z 344.2596) has the empirical molecular formula C 22 H 35 NO 5 and produced fragment ions at m/z 326.2458 [M + H − H 2 O] + and 300.1997 [M + H – CH 2 CHOH] + at 375 V, indicating that it could have one hydroxyl and ‐CH 2 CH 2 OH at the periphery of the skeleton.…”
Section: Tofms Fragmentation Behaviormentioning
confidence: 52%
“…When the fragmentor voltage increased to 375 V, it produced three minor fragment ions at m/z 312.1974, 294.1865 and 266.1867 by consecutive losses of H 2 O, H 2 O and CO. Compared with the literature reports (Rashkes et al , ; Bessonova and Saidkhodzhaeva, ), it could be tentatively identified as hetisine. Compound 14 ( m/z 344.2596) has the empirical molecular formula C 22 H 35 NO 5 and produced fragment ions at m/z 326.2458 [M + H − H 2 O] + and 300.1997 [M + H – CH 2 CHOH] + at 375 V, indicating that it could have one hydroxyl and ‐CH 2 CH 2 OH at the periphery of the skeleton.…”
Section: Tofms Fragmentation Behaviormentioning
confidence: 52%
“…Phytochemically, more than 197 diterpenoid alkaloids (DA) with complicated structures have been isolated from 56 Aconitum species of pharmacological significance 13 14 15 . These Aconitum DA have been reported to possess a broad range of bioactivities including anti-inflammatory properties 3 9 16 17 18 19 20 21 .…”
mentioning
confidence: 99%
“…Aconitum spp. (monkshood) is one of the most extracted and isolated sources of DAs, where more than half of natural DAs were isolated from [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%